ANALISIS SEMIOTIKA DARK JOKE DAN SATIRE COKI PARDEDE DI MEDIA SOSIAL INSTAGRAM - Akhmad Khoirul Amir; Fatihatul Lailiyah; Masnia Ningsih (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2021)
Communication is currently growing with the existence of communication technology. New media are constantly being created so that the flow of communication is increasing. According to McLuhan, new media affect humans in communicating and the way they communicate affects human life. Now humans can share and communicate using social media with various motivations. Humor is one of the things that is often used in social media where ideas, opinions, and various other expressions are wrapped in humor. One of the most common uses of humor found in popular social media such as Instagram and Twitter. Like a comedian or stand-up comedian Coki Pardede who often makes dark jokes and satire on his social media. So the title of this research is "Analysis of Semiotics of Dark jokes and Coki Pardede's Satire on Instagram Social Media". The purpose of this study is to find out the meaning contained in dark jokes and satire on Coki Pardede's Instagram. By using content analysis techniques and semiotic analysis theory initiated by Charles Sanders Peirce. With the results of the study, namely knowing the meaning of dark jokes and satire on Instagram.